Bioenergy futures in Sweden – Modeling integration scenarios for biofuel production. (15th August 2016) - Börjesson Hagberg, Martin; Pettersson, Karin; Ahlgren, Erik O.
Abstract: Use of bioenergy can contribute to greenhouse gas emission reductions and increased energy security. However, even though biomass is a renewable resource, the potential is limited, and efficient use of available biomass resources will become increasingly important. This paper aims to explore system interactions related to future bioenergy utilization and cost-efficient bioenergy technology choices under stringent CO2 constraints. In particular, the study investigates system effects linked to integration of advanced biofuel production with district heating and industry under different developments in the electricity sector and biomass supply system. The study is based on analysis with the MARKAL_Sweden model, which is a bottom-up, cost-optimization model covering the Swedish energy system. A time horizon to 2050 is applied. The results suggest that system integration of biofuel production has noteworthy effects on the overall system level, improves system cost-efficiency and influences parameters such as biomass price, marginal CO2 emission reduction costs and cost-efficient biofuel choices in the transport sector. In the long run and under stringent CO2 constraints, system integration of biofuel production has, however, low impact on total bioenergy use, which is largely decided by supply-related constraints, and on total transport biofuel use, which to large extent is driven by demand. Highlights: Long-term bioenergy scenarios for Sweden are modeled. Efficient use of biomass resources will become increasingly important. Integration of biofuel production with industry or heating improves efficiency. Integration can reduce biomass prices and marginal CO2 reduction costs. Cost-efficient biofuel choices in the transport sector are affected.